2014
DOI: 10.1177/0886260514534525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Experiences of Intimate Partner Violence Against Women With Disabilities in Bangladesh

Abstract: This study was aimed to estimate the prevalence of intimate partner violence (IPV) in a sample of 226 women with disabilities living in four different districts of Bangladesh. It also explored the physical and psychological suffering of women experiencing violence and their various coping strategies. A cross-sectional survey was carried out with 226 women with disabilities to measure the prevalence of IPV, and 16 in-depth interviews were conducted to document in detail the experiences of violence encountered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Accordingly, it was not possible to determine if disability was present at the time the violence was experienced. This approach has also been reported in previous cross‐sectional research 10,16,29,35–37 . Considering that violence in the past 12 months is a relatively rare event, extended time frames are necessary to capture a sufficient number of cases for detailed analysis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Accordingly, it was not possible to determine if disability was present at the time the violence was experienced. This approach has also been reported in previous cross‐sectional research 10,16,29,35–37 . Considering that violence in the past 12 months is a relatively rare event, extended time frames are necessary to capture a sufficient number of cases for detailed analysis.…”
Section: Discussionmentioning
confidence: 88%
“…Internationally, there is considerable evidence that that poverty and disadvantage increases the risk of violence 9 . In Australia, as in other high income countries, people with disabilities are more likely to have lower levels of education, lower incomes and higher levels of unemployment 2 and there is some evidence internationally to suggest that poverty contributes to increased risk of violence among people with disabilities 13,28,29 . In addition, people with disabilities are often exposed to other risk factors for violence, such as: living in institutions; being dependent on informal or formal care in the home; 28 reduced physical and emotional defences; communication barriers that hamper reporting of violence; social stigma; and discrimination 4 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, women continue to be victims of physical violence or domestic abuse by their partners, relatives or neighbors and this may have an impact on the prevalence of disability. A study conducted into the experience of 226 disabled women residing in different districts in Bangladesh found that 84% of them had suffered physical and psychological problems due to at least one form of violence including emotional abuse and physical, verbal or sexual violence from their partners during their lifetime [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Our next projects will be built on this study to examine women's (1) triple intersectional locations, especially the intersecting locations of younger age-lower education-poverty and (2) community-level locations. Examining the effects of other locations such as ethnicity, disability, non-heterosexual and dating relationships, and slums (Hadi, 2011;Hasan, Muhaddes, Camellia, Selim, & Rashid, 2014;Kelly, 2011;Rashid, 2006) are important, but it is beyond the scope of this study. With a cross-sectional design, we have examined only the association between women's different intersectional locations and MIPPV, not the causality.…”
Section: Strengths and Limitationsmentioning
confidence: 99%